Malignant triton tumor of the neck: A case report - Agustina, Sisca Dwi; Reksoprawira, Sunarto; Pasaribu, Ulinta Purwati; Kusumastuti, Etty Hari (Edelweiss Applied Science and Technology, 2025)
Malignant Triton tumor (MTT) is a rare variant of Malignant Peripheral Nerve Sheath Tumors (MPNST) with striated muscle formation. The diagnosis of MTT must meet the diagnostic criteria of MPNST and proven rhabdomyoblast differentiation. This case is discussed because of its rare incidence, which is 5-10% of all MPNSTs. The prognosis in most MTT patients is poor due to its rarity. Malignant Triton tumor (MTT) is a rare variant of malignant peripheral nerve sheath tumor. A 34-year-old woman came to the Head and Neck Surgery clinic of RSUD Dr. Soetomo Surabaya with complaints of a lump on the left upper front neck. This painless lump was small, marble-sized, skin-colored, and had enlarged rapidly over the last year. On physical examination, a skin-colored mass was found in the anterior colli region sinistra, which extended to the infraauricula sinistra, measuring approximately 20 x 20 x 15 cm with a hard solid consistency, partially spongy, flat surface, and indistinct borders. The patient underwent wide excision, vascular exploration, and continued with radiotherapy. The prognosis in most MTT patients is poor, and due to its rarity, studies with a large number of cases are lacking. MTT is a rare variant of MPNST with rhabdomyoblastic differentiation that behaves more aggressively than typical MPNST, thus having a worse prognosis. Treatment modalities, especially in advanced and metastatic cases, still lack standardized management or guidelines for the management of MTT. Until now, surgical excision and adjuvant radiotherapy have been the main therapeutic options for MTT.